$k$-Snakes in finite-order interpolational classes of functions - Ivashchuk, Ya. G. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
$k$-snakes are a generalization of the polynomials with the least deviation from zero underk-constraints. We prove the existence and uniqueness of $k$-snakes in finite-order interpolational classes and their continuous differentiability with respect to a parameter.